Characterisation of cellular and humoral autoimmune responses to histone H1 and core histones in human systemic lupus erythaematosus. Issue 1 (28th March 2008) - Stummvoll, G H; Fritsch, R D; Meyer, B; Hoefler, E; Aringer, M; Smolen, J S; Steiner, G
Abstract : Objective: To address key aspects of anti-histone autoimmunity in systemic lupus erythaematosus (SLE), we performed a detailed characterisation of cellular and humoral autoreactivity to histone H1 and the four core histones H2A, H2B, H3, H4 in patients with SLE and healthy controls. Methods: Peripheral blood mononuclear cells of 41 patients with SLE and 28 healthy controls were exposed to individual histones and proliferation was measured by [ 3 H]-thymidine incorporation. H1-reactive T cell clones were obtained by limiting dilution. Cytokines and total IgG in culture supernatants was measured by ELISA, and autoantibodies to histones were determined by ELISA and immunoblotting. Results: Proliferative responses to H1 were more frequent and more pronounced in cell cultures from patients with SLE (p<0.002), while among the core histones only the response to H2A was increased in patient cultures (p<0.01). All histones elicited a Th1-like cytokine response in patients and controls (high interferon (IFN)γ and tumour necrosis factor (TNF)α, no interleukin (IL)4) with H1 inducing the highest levels of TNFα. However, H1 stimulated production of IgG and anti-histone antibodies only in cell cultures derived from patients with SLE. H1-specific T cell clones from patients and controls showed a CD4+CD28+ phenotype and a Th1 cytokine profile. Anti-histone antibodies were detected in 51% of patients with SLE, were primarily directed to H1, H3 and H4, and predominantly of the IgG2 subtype. Conclusions: Histone H1 constitutes a major B cell and T cell autoantigen in SLE, triggering a proinflammatory Th1 response and driving autoantibody production. This suggests that histone H1 may be of considerable relevance for the pathogenesis of SLE.